Utility of pleural fluid adenosine deaminase in diagnosing tubercular pleural effusion: a prospective observational study in a tertiary care hospital - H. J., Gayathri Devi; H., Sujith (International Journal of Advances in Medicine, 2019)
Background: The diagnosis of Tubercular (TB) pleural effusion continues to be a challenge in clinical practice, as traditional diagnostic methods are useful but do not provide enough sensitivity and specificity. Methods: This was a prospective observational study carried out at Tertiary care Hospital with study population of 76 patients. Etiological diagnosis was based on clinical history with radiological imaging, biochemical and cytological examination of pleural fluid. Pleural fluid ADA was used as a biomarker for the diagnosis of tubercular pleural effusion. Results: The study included 76 patients with 69.7% (n=53) males and 30.3%(n=23) females. The mean age of patients was 48.97 17.03 years. Of 76 cases of pleural effusion, 62 were exudates and 14 transudates. Tuberculosis was the most common cause among exudates which accounted for 51.3% (n=39) of cases. The sensitivity, specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV), Accuracy of pleural fluid ADA in diagnosing tubercular pleural effusion was 92.3%, 97.3%, 97%, 92% and 94.7% respectively. Conclusions: Pleural fluid ADA can be one of the most reliable biomarkers for the diagnosis of TB pleural effusion considering its high sensitivity and specificity.